2016
DOI: 10.1039/c5fo01258a
|View full text |Cite
|
Sign up to set email alerts
|

Bioefficacy of Graviola leaf extracts in scavenging free radicals and upregulating antioxidant genes

Abstract: The aims of this study were to determine bioactive components of Graviola leaf extracts and to examine the radical scavenging capacity, gene expression of antioxidant enzymes and transcription factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 43 publications
0
28
0
2
Order By: Relevance
“…Besides, Graviola leaf contains various phytoconstituents such as alkaloids, flavonol triglycosides, phenolics, cyclopeptides, and essential oils [6, 13, 24]. Recently, we found that Graviola contains high concentrations of rutin, kaempferol-rutinoside, and vitamin U and effectively scavenged peroxyl and nitrogen radicals [14]. In addition, Graviola reduced the production of reactive oxygen species (ROS).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Besides, Graviola leaf contains various phytoconstituents such as alkaloids, flavonol triglycosides, phenolics, cyclopeptides, and essential oils [6, 13, 24]. Recently, we found that Graviola contains high concentrations of rutin, kaempferol-rutinoside, and vitamin U and effectively scavenged peroxyl and nitrogen radicals [14]. In addition, Graviola reduced the production of reactive oxygen species (ROS).…”
Section: Discussionmentioning
confidence: 99%
“…It was then stored at −20°C until use for analysis. Bioactive components in standardized GE were analyzed by LC-MS/MS as reported previously [14]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The oxygen radical absorbance capacity (ORAC) assay was applied to assess the peroxy radical (ROO · ) scavenging capacity of LCL extracts according to Son et al The relative fluorescence intensity (percent) was detected every 5 min by using a microplate reader (Thermo Scientific) until the fluorescence reading was below 5% of the initial fluorescent light absorbance.…”
Section: Methodsmentioning
confidence: 99%